2013
DOI: 10.1136/gutjnl-2012-303852
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ribavirin on viral kinetics and liver gene expression in chronic hepatitis C

Abstract: Objective Ribavirin improves treatment response to pegylated-interferon (PEG-IFN) in chronic hepatitis C but the mechanism remains controversial. We studied correlates of response and mechanism of action of ribavirin in treatment of hepatitis C. Design 70 treatment-naïve patients were randomized to 4 weeks of ribavirin (1000–1200 mg/d) or none, followed by PEG-IFN alfa-2a and ribavirin at standard doses and durations. Patients were also randomized to a liver biopsy 24 hours before, or 6 hours after starting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
77
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(89 citation statements)
references
References 26 publications
11
77
1
Order By: Relevance
“…It is conceivable that the clinical effect of ribavirin may be at least partially mediated by resetting the IFN responsiveness in the liver (14). In conclusion, this explorative study analyzed ribavirin-induced mutations with high sensitivity and demonstrated that ribavirin induces nucleotide transitions during monotherapy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is conceivable that the clinical effect of ribavirin may be at least partially mediated by resetting the IFN responsiveness in the liver (14). In conclusion, this explorative study analyzed ribavirin-induced mutations with high sensitivity and demonstrated that ribavirin induces nucleotide transitions during monotherapy.…”
Section: Discussionmentioning
confidence: 97%
“…It was recently shown that ribavirin in conjunction with IFN-␣/PEG-IFN-␣ induces the expression of specific interferon-stimulated genes (ISGs) in vitro and in vivo, thereby potentiating the anti-HCV effect of interferon (12)(13)(14). Other possible mechanisms of ribavirin action include the following models: strengthening of the adaptive antiviral immune response, impairment of the cellular enzyme IMP dehydrogenase (IMPDH), direct inhibition of the HCV nonstructural 5B (NS5B) RNA-dependent RNA polymerase, and exertion of a mutagenic effect on RNA viruses and the resulting error catastrophe (15,16).…”
mentioning
confidence: 99%
“…Control liver biopsies were obtained from 5 nondiabetic patients (mean age, 47 years; n = 3 female patients) who had a past history of chronic hepatitis C and were successfully treated with viral eradication at least 6 months prior to the biopsy (64). Histological evaluation of these samples revealed no signs of steatosis or hepatic inflammation or injury.…”
Section: Discussionmentioning
confidence: 99%
“…According to Rotman et al Ribavirin monotherapy decreases IP-10 serum levels, but it has no effect on ISG expression in PBMC (Peripheral blood mononuclear cell) (19). The available data on the effect on viremia and sustained response of 4-6 weeks pretreatment with Ribavirin before the standard bi-therapy with Peg-interferon are controversial (19,20,21,22,23,24,25,26,27).…”
Section: Introductionmentioning
confidence: 99%
“…The available data on the effect on viremia and sustained response of 4-6 weeks pretreatment with Ribavirin before the standard bi-therapy with Peg-interferon are controversial (19,20,21,22,23,24,25,26,27). Administration of the drug within 6 months after a standard bi-therapy does not improve response (28).…”
Section: Introductionmentioning
confidence: 99%